Changes in the Hematopoietic System and Blood Under the Influence of Heavy Metal Salts Can Be Reduced with Vitamin E - Anatolii ROMANIUK; Mykola LYNDIN; Yulia LУNDІNA; Vladyslav SIKORA; Natalia HRINTSOVA; Olena TIMAKOVA; Olena GUDYMENKO; Oksana GLADCHENKO (Federation of Turkish Pathology Societies, 2018)
Objective: The aim of our work was to study the blood parameters and bone marrow morphological changes in rats exposed to increased amounts of heavy metal salts and the effect of vitamin E. Material and Method: Investigation of bone marrow structural features and blood parameters was performed in sexually mature Wistar male rats (n=84). Results: Exposure to increased amounts of heavy metal salts led to the inhibition of erythropoiesis and leukopoiesis, as well as a synchronized increase in the number of megakaryocytes which was clearly reflected in the blood: the number of erythrocytes, leukocytes and Hb decreased, and the number of platelets increased. These changes in the blood and bone marrow were less pronounced when vitamin E was used as an adjuster. Conclusion: When increased amounts of HMS enter the rats` bodies, suppression of erythropoiesis and leukocytopoiesis occurs while thrombocytopoiesis increases. These changes depend on the period of intake of heavy metal salts. The adjustment of vitamin E reduces the severity of the cytotoxic effect of heavy metals and improves readaptation in the recovery period.